Cloning of medicinal plants through tissue culture--a review - Chaturvedi, H C; Jain, Madhu; Kidwai, N R (Indian journal of experimental biology, 2007)
In order to have standardized formulations, the chemical constituents from plants and their parts are required to be uniform both qualitatively and quantitatively. Furthermore, an ever increasing demand of uniform medicinal plants based medicines warrants their mass cloning through plant tissue culture strategy. A good number of medicinal plants have been reported to regenerate in vitro from their various parts, but a critical evaluation of such reports reveals that only a few complete medicinal plants have been regenerated and still fewer have actually been grown in soil, while their micropropagation on a mass scale has rarely been achieved, particularly in those medicinal plants where conventional propagation is inadequate, like, the mass clonal propagation of Dioscorea floribunda leading to its successful field trials. Such facts make it imperative to document the factual position of micropropagation of medicinal plants bringing out the advancements made along with the short falls, in this important area. The present review deals with the futuristic view on the said subject restricted to higher plants.